2012
DOI: 10.1038/nature11228
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 links amino acid malnutrition to microbial ecology and intestinal inflammation

Abstract: Malnutrition affects up to one billion people in the world and is a major cause of mortality. In many cases, malnutrition is associated with diarrhoea and intestinal inflammation, further contributing to morbidity and death. The mechanisms by which unbalanced dietary nutrients affect intestinal homeostasis are largely unknown. Here we report that deficiency in murine angiotensin I converting enzyme (peptidyl-dipeptidase A) 2 (Ace2), which encodes a key regulatory enzyme of the renin-angiotensin system (RAS), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
1,134
2
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,139 publications
(1,198 citation statements)
references
References 43 publications
39
1,134
2
23
Order By: Relevance
“…In the mouse, the absence of (a) Rag2 and T-bet, (b) the angiotensin-converting enzyme 2 (ACE2), or (c) the Nod-like receptor pyrin domaincontaining protein 6 is known to predispose to the emergence of transmissible, disease-predisposing commensals (26,36,37). Understanding how the gut mucosa discriminates between disease-predisposing microorganisms and mutualists may provide insights into disease onset and tumor progression in genetically predisposed individuals and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, the absence of (a) Rag2 and T-bet, (b) the angiotensin-converting enzyme 2 (ACE2), or (c) the Nod-like receptor pyrin domaincontaining protein 6 is known to predispose to the emergence of transmissible, disease-predisposing commensals (26,36,37). Understanding how the gut mucosa discriminates between disease-predisposing microorganisms and mutualists may provide insights into disease onset and tumor progression in genetically predisposed individuals and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…A similar interaction with ACE2 has been proposed for the L-proline transporter SIT1 the defects of which contributes to iminoglycinuria . The deficiency of ACE2 impairs amino acid absorption in the mouse, in particular of tryptophan, and thereby increases susceptibility to intestinal inflammation (Hashimoto et al 2012). In rodent heart, kidney and aorta, treatment with ACEIs and/or ARBs was shown to increase ACE2 expression (Chappel and Ferrario 2006;Ferrario and Varagic 2010;Igase et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…37, 90 In addition to Hartnup's disorder, a recent study by our group revealed that ACE2 regulates intestinal epithelial immunity by controlling amino acid homeostasis, expression of antimicrobial peptides, and the ecology of the gut microbiome. 91 The finding can molecularly explain why amino acid malnutrition can cause intestinal inflammation and diarrhea. Because such RAS-independent functions of ACE2 have not yet been observed in cardiovascular systems, such as hearts, kidneys, and blood vessels, further studies are warranted.…”
Section: Ace2 In Hartnup's Disorder and Intestinal Epithelial Immunitymentioning
confidence: 99%